2013
DOI: 10.15628/holos.2013.1479
|View full text |Cite
|
Sign up to set email alerts
|

Uso De Drogas E Desempenho Escolar Entre Jovens E Adolescentes Do Ensino Médio De Uma Escola Pública De Pires Do Rio – Go

Abstract: RESUMOEste estudo teve como objetivo estimar a prevalência do uso de drogas por discentes de uma escola da rede estadual de Pires do Rio, Goiás, associando-a ao desempenho escolar dos mesmos. Participaram da pesquisa 371 discentes do ensino médio, com idade entre 14 e 34 anos, dos turnos matutino e noturno que responderam a um questionário anônimo coletivamente em sala de aula. As drogas mais consumidas, alguma vez na vida, foram: álcool (95,8%), tabaco (46,1%), maconha (3,5%), solventes (4%), cocaína (4%) e c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…In this research, most students reported having experienced psychoactive substances at least once (“use in life”), and alcohol was the most mentioned, which corroborates previous work 5 , 7 , 13 . This result seems a worldwide reality, identified in Zambia and Uganda 20 , Portugal 14 , Spain 21 , Argentina 16 , and Mexico 22 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this research, most students reported having experienced psychoactive substances at least once (“use in life”), and alcohol was the most mentioned, which corroborates previous work 5 , 7 , 13 . This result seems a worldwide reality, identified in Zambia and Uganda 20 , Portugal 14 , Spain 21 , Argentina 16 , and Mexico 22 .…”
Section: Discussionsupporting
confidence: 90%
“…Villegas-Pantoja et al 22 have observed that, among psychoactive substances, the most consumed are alcohol and cigarettes. In addition, Brazilian studies have shown that the third most commonly used substance is marijuana 5 , 7 , 13 .…”
Section: Discussionmentioning
confidence: 99%